2022
DOI: 10.1038/s41467-022-31430-0
|View full text |Cite
|
Sign up to set email alerts
|

The genetic heterogeneity and drug resistance mechanisms of relapsed refractory multiple myeloma

Abstract: Multiple myeloma is the second most common hematological malignancy. Despite significant advances in treatment, relapse is common and carries a poor prognosis. Thus, it is critical to elucidate the genetic factors contributing to disease progression and drug resistance. Here, we carry out integrative clinical sequencing of 511 relapsed, refractory multiple myeloma (RRMM) patients to define the disease’s molecular alterations landscape. The NF-κB and RAS/MAPK pathways are more commonly altered than previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…A limitation of our study was the unrelatedness of the ndMM and rrMM cohorts. We 6 and others 5 , 52 , 53 have shown that sequential sampling is the ideal approach for analyzing clonal dynamics. Detection of subclones that predict relapse might enable investigation of change of therapy and thus their appearance or expansion must be carefully considered as we plan the trials and therapeutic approaches of the future.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study was the unrelatedness of the ndMM and rrMM cohorts. We 6 and others 5 , 52 , 53 have shown that sequential sampling is the ideal approach for analyzing clonal dynamics. Detection of subclones that predict relapse might enable investigation of change of therapy and thus their appearance or expansion must be carefully considered as we plan the trials and therapeutic approaches of the future.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, the potentially APOBEC3-induced C > T EGFR T790 mutation can promote resistance to the EGFR inhibitors gefitinib and erlotinib [ 82 , 141 ]. Similarly, some APOEBC3-induced mutations observed in relapsed refractory multiple myeloma may contribute to acquire therapy resistance [ 158 ].…”
Section: Impact Of Apobec3s Through Mutagenic and Non-mutagenic Pathwaysmentioning
confidence: 99%
“…Moreover, APOBEC3s could be particularly fruitful biomarkers for targeted therapies (Table 6 ). High APOBEC3B expression has been associated with poor response to Raf inhibitors in glioma, and certain APOBEC3-induced mutations may predict resistance to Raf inhibitors and EGFR inhibitors in multiple myeloma and lung cancer, respectively [ 82 , 158 ]. In ER + breast cancer, high APOBEC3B expression can predict resistance to the endocrine therapy tamoxifen [ 192 ].…”
Section: Clinical and Therapeutic Significance Of Apobec3s In Cancersmentioning
confidence: 99%
“…146 The authors also discovered a point mutation that affected codons 221-250, and disrupted most of the CD38 epitopes bound by daratumumab, thus facilitating the evasion of MM cells from daratumumab. 146 Theoretically, the mechanism of action of isatuximab would not be affected by this point mutation, as the epitope of isatuximab is composed of residues from codons 34-189. 146 No mutations in CD38 have been reported to impact isatuximab binding.…”
Section: Tumor Intrinsic Resistance Mechanismsmentioning
confidence: 99%